2020
DOI: 10.1073/pnas.1920131117
|View full text |Cite
|
Sign up to set email alerts
|

Individual differences in trust evaluations are shaped mostly by environments, not genes

Abstract: People evaluate a stranger’s trustworthiness from their facial features in a fraction of a second, despite common advice “not to judge a book by its cover.” Evaluations of trustworthiness have critical and widespread social impact, predicting financial lending, mate selection, and even criminal justice outcomes. Consequently, understanding how people perceive trustworthiness from faces has been a major focus of scientific inquiry, and detailed models explain how consensus impressions of trustworthiness are dri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
113
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(131 citation statements)
references
References 45 publications
(74 reference statements)
9
113
1
Order By: Relevance
“…We correlated participants’ initial ratings of 100 images and subsequent ratings of the same images and found good consistency in participant judgements. However, our test–retest correlations were weaker than those of other recent studies (e.g., Kramer et al., 2018; Sutherland et al., 2020); it is not clear why this was the case. Researchers should strive to include test–retest reliability measures in their studies to shed light on factors that influence within-participant consistency in trait judgements.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We correlated participants’ initial ratings of 100 images and subsequent ratings of the same images and found good consistency in participant judgements. However, our test–retest correlations were weaker than those of other recent studies (e.g., Kramer et al., 2018; Sutherland et al., 2020); it is not clear why this was the case. Researchers should strive to include test–retest reliability measures in their studies to shed light on factors that influence within-participant consistency in trait judgements.…”
Section: Discussioncontrasting
confidence: 99%
“…Therefore, if some traits are predominately derived from stable cues (e.g., attractiveness), and if stable cues are used to recognise an identity, then trait impressions might share common underlying processes with facial recognition. Researchers may wish to extend upon Sutherland et al.’s (2020) work by investigating the relationship between trait judgements and recognition performance across multiple images of the same face. Future research should also explore how trustworthiness, dominance, and attractiveness relate to processes underlying facial recognition.…”
Section: Discussionmentioning
confidence: 99%
“…Hence, we believe that what is shared is not shared because of environmental influence but because of a common inheritance that leads to common brain concepts. Our belief is strengthened not only by the results of this study, but also by studies that have shown that infants tend to look more at faces that are reliably classified as attractive by adult individuals (Slater et al, 1998). We note that although our participants were drawn from 19 countries, most were nevertheless from Western countries.…”
Section: Discussionsupporting
confidence: 58%
“…Studies involving bigger sample sizes and specifically designed to address this issue are needed to further understand how gender, other personal traits, as well as socialization and personal experiences, relate to the interpretation of (un)reliable prosodic displays. Relatedly, recent research involving twins showed that face impressions of trustworthiness are mostly determined by personal experiences rather than genes or shared environments 70 .…”
Section: Discussionmentioning
confidence: 99%